2017
DOI: 10.1016/j.pedneo.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing enterocolitis in low birth weight infants in China: Mortality risk factors expressed by birth weight categories

Abstract: Necrotizing enterocolitis remains an important cause of morbidity and mortality in prematurely born neonates in Chinese neonatal units. Awareness of the associated risk factors and appropriate interventions may improve the outcome of necrotizing enterocolitis in different birth weight subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 29 publications
3
27
4
2
Order By: Relevance
“…Multiple studies were also reported from the Europe including Poland, Romania, Finland, Belgium, Sweden and Switzerland [12,13,23,39,42,43]. Also, four studies were done in China, Korea, Singapore and Malaysia [14,16,44,45]. Three studies from Australia [4,21,46], one from the Middle East [7] and one from India [24].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies were also reported from the Europe including Poland, Romania, Finland, Belgium, Sweden and Switzerland [12,13,23,39,42,43]. Also, four studies were done in China, Korea, Singapore and Malaysia [14,16,44,45]. Three studies from Australia [4,21,46], one from the Middle East [7] and one from India [24].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Qian et al reported data extracted retrospectively from 95 major referral centers and hospitals in china covering a large area of 29 provinces [44]. VLBW infants were specified and the incidence of NEC according to Bell's criteria was presented in 2011.…”
Section: Qualitative Reviewmentioning
confidence: 99%
“…Multiple studies were also reported from the Europe including Poland, Romania, Finland, Belgium, Sweden and Switzerland (12,13,28,(32)(33)(34). Also, four studies were done in China, Korea, Singapore and Malaysia (14,16,35,36). Three studies from Australia (4,37,38), one from the Middle East (7) and one from India (42).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Also, four studies were done in China, Korea, Singapore and Malaysia (14,16,35,36). Three studies from Australia (4,37,38), one from the Middle East (7) and one from India (42).…”
Section: Study Characteristicsmentioning
confidence: 99%